An agent-based model for cruise ship evacuation considering the presence of smart technologies on board. (15th March 2023) - Cotfas, Liviu-Adrian; Delcea, Camelia; Mancini, Simone; Ponsiglione, Cristina; Vitiello, Luigi
Highlights: The impact of using smart technologies in ship evacuation is evaluated. An agent-based model is created for capturing and simulating the flow of passengers. Several scenarios featuring various weather and ship conditions are considered. Different levels of smart technologies adoption are analyzed. Guidance application has a positive impact on the average evacuation time. Abstract: The cruise ship industry has faced in recent years a continuous increase in the number of passengers, reaching 28.5 million passengers in 2018, 60.11% more than in 2009. In this context, the research literature has acknowledged the key role played by the passengers' safety and has considered different aspects when dealing with the ship evacuation process related to both environmental properties and human behavioral aspects. Cruise ship companies have manifested a real interest in offering their passengers a safe travel experience and have continuously considered and adapted their evacuation plans to support a faster evacuation process. With the enhancement of technology, cruise ship companies can contribute more to increase safety during an emergency evacuation by providing smartphone applications that can assist each passenger involved in this process. As a result, the present paper aims to measure the impact made by the use of such an application on evacuation time by considering various weather conditions, ship conditions, and different times of the day. According to this purpose, an agent-based model is created for simulating the evacuation process of a ship deck which could accommodate up to 1200 people . The results indicate that using an application reduces the average evacuation time, with a 70% increase in usage leading to a 34.5% reduction in evacuation time. The main contribution of this work is to apply agent-based modelling to analyze the evacuation behavior on cruise ships when smart technologies are available, incorporating in the analysis elements and characteristics that have been previously considered in isolation. The model can be used as a support laboratory for policy advice: it can be applied for estimating the evacuation movement time under various conditions and for different levels of application adoption, as well as for assisting the decision-makers in designing the emergency plans and making the right decisions related to cruise ship evacuation.